Saving by default: Evidence from a field experiment in rural India - Vincent Somville; Lore Vandewalle (Graduate Institute of International and Development Studies, 2016)
Worldwide, people are gaining access to a formal bank account, which allows account-based instead of cash payments. Based on a novel randomized control trial, we document that the payment method is an important determinant of savings behavior. In rural India, we study the effect on savings of allocating identical weekly payments on a bank account (treated) or in cash (control). The treatment impact is huge: savings increase by 110% within three months, and the effect is long-lasting. Villagers paid in cash do not save more in other assets, but increase consumption. Therefore, we infer that being paid on a bank account has a net positive impact on total savings. When we twist the design and start paying everyone in cash, savings and consumption patterns no longer differ between the treated and control. We interpret these findings as the outcome of the default option, and shed light on six plausible underlying mechanisms.
Keywords: D14; C93; D03; G21; O16; 330; Sparen; Finanzielle Inklusion; Einlagengeschäft; Konsumentenverhalten; Ländlicher Raum; Indien